SecureDBaaS Model for Accessing Encrypted Cloud Databases - Palle Jagadeeswaraiah; M.R. Pavan Kumar (Institute of Advanced Engineering and Science, 2015)
Cloud computing has recently emerged being a compelling paradigm that pertains to managing and delivering services over the web. The particular prevalent problem connected with cloud is confidentiality, security, as well as reliability etc., in which how the cloud provider assures. To recognize this, a novel architecture is usually introduced that will integrates cloud database services and as well executing concurrent operations on encrypted information. Also a new homomorphic encryption algorithm will likely be incorporated to offer confidentiality as well as concurrent execution of various SQL operations. This will be the first option supporting quite a few distributed clienteles to access encrypted cloud databases. One of main thing is that it eliminates advanced proxies in between cloud user and provider.The performance on the architecture is usually calculated by means of theoretical and practical results which are subjected to TPC-C benchmark standard tools for a number of clients as well as network latencies.